Chemical Genetics Screen Identifies Epigenetic Mechanisms Involved in Dopaminergic and Noradrenergic Neurogenesis in Zebrafish - Westphal, Markus; Sant, Pooja; Hauser, Alexander-Thomas; Jung, Manfred; Driever, Wolfgang (Frontiers in Genetics, 2020)
The cell type diversity and complexity of the nervous system is generated by a network of signaling events, transcription factors, and epigenetic regulators. Signaling and transcriptional control have been easily amenable to forward genetic screens in model organisms like zebrafish. In contrast, epigenetic mechanisms have been somewhat elusive in genetic screens, likely caused by broad action in multiple developmental pathways that masks specific phenotypes, but also by genetic redundancies of epigenetic factors. Here, we performed a screen using small molecule inhibitors of epigenetic mechanisms to reveal contributions to specific aspects of neurogenesis in zebrafish. We chose development of dopaminergic and noradrenergic neurons from neural progenitors as target of epigenetic regulation. We performed the screen in two phases: First, we tested a small molecule inhibitor library that targets a broad range of epigenetic protein classes and mechanisms, using expression of the dopaminergic and noradrenergic marker tyrosine hydroxylase as readout. We identified ten compounds, including HDAC, Bromodomain and HAT inhibitors, which interfered with dopaminergic and noradrenergic development in larval zebrafish. In the second screening phase, we aimed to identify neurogenesis stages affected by these ten inhibitors. We analyzed treated embryos for effects on neural stem cells, growth progression of the retina, and apoptosis in neural tissues. In addition, we analyzed effects on islet1 expressing neuronal populations to determine potential selectivity of compounds for transmitter phenotypes. In summary, our targeted screen of epigenetic inhibitors identified specific compounds, which reveal chromatin regulator classes that contribute to dopaminergic and noradrenergic neurogenesis in vivo.